Transitional Economies Banking, Finance, Institutions - Kalyuzhnova, Yelena; Taylor, Michael (Palgrave Macmillan UK, 2001)
The integration of the countries of Central and Eastern Europe and the Commonwealth of Independent States international financial system was arguably one of the most profound changes experienced by the world economy in the 1990s. This book examines these countries in reforming their financial systems in the fist decade of transition. Through case studies as well as more thematic approaches contributors deal with crucial elements of building a market-based financial system, the transformation of the banking sector, and non-bank reform and regulation of financial markets. They emphasise the importance of institution-building to the process of financial sector transformation and highlight the lessons to be learned from transitional financial experiences